Relevance of Microfinance Banks in Financing of Small and Medium Entrepreneurs in Nigeria - Ibrahim, Sani (NIU Journal of Social Sciences; Vol 3 No 1 (2017): KIU Journal of Social Sciences, Vol. 3 No. 1, March 2017, 2017)
This study investigated the relevance of microfinance banks in the financing of small and medium entrepreneurs in Sabon Gari Local Government Area of Kaduna State, Nigeria. Survey research design was used in conducting the study. The study had two null hypotheses. Questionnaire was used to obtain data from twenty four small and medium entrepreneurs. Pearson Product Moment Correlation statistic was used to test the null hypotheses at 0.05 level of significance. The findings revealed that microfinance banks had no significant relevance in the financing of both small and medium entrepreneurs in Sabon Gari Local Government Area of Kaduna State, Nigeria. The study concluded that microfinance banks had not impacted on the finances of small and medium entrepreneurs in Sabon Gari Local Government Area of Kaduna State, Nigeria. Based on the findings, two recommendations were made; microfinance banks should be more involved in the financing of small entrepreneurs in Sabon Gari Local Government Area of Kaduna State; microfinance banks should be more involved in the financing of medium entrepreneurs in Sabon Gari Local Government Area of Kaduna State, Nigeria. Keywords: Microfinance Banks, Entrepreneurs, Financing